2006
DOI: 10.1080/00207590500492625
|View full text |Cite
|
Sign up to set email alerts
|

Operant conditioning and errorless learning procedures in the treatment of chronic aphasia

Abstract: I n the field of aphasia, the processes that enable improvements in fluent speech, e.g., in naming, reading, sentence structure, etc., are not well understood. At the present time the fields of cognitive psychology, clinical neuropsychology, and cognitive neuropsychology are limited with regard to explaining the causes of different symptoms of aphasia. Treatment based on operant conditioning or stimulus control procedures seems to be very promising. In the present study, four participants with chronic aphasia,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 16 publications
0
9
0
2
Order By: Relevance
“…SLPs even employ many of the same practices as behavior analysts, including the frequent use of single‐subject analysis (Thompson, 2006), antecedent manipulation (i.e., prompting, modeling; Keenan, 1966; Lowell et al., 1995, Thompson et al., 2006), fading (Salvatore, 1976; Melodic Intonation Therapy [MIT]; Sparks & Holland, 1976), shaping (Holland & Harris, 1968; Silkes et al., 2019), and consequence delivery (Goldfarb, 2006; Holland & Harris, 1968; Kushner et al., 1973). This SLP work provides additional empirical support for the efficacy of operant techniques in aphasia treatment that is also demonstrated in purely behavioral work (e.g., chaining, delayed feedback, socially and self‐mediated consequences, and differential reinforcement; Doyle et al., 1989; Goodkin, 1969; Porsteinsson & Sigurðardóttir, 2007; Sigurðardóttir & Sighvatsson, 2006, 2011; Sundberg et al., 1990).…”
Section: A Behavioral Approach To the Treatment Of Aphasiamentioning
confidence: 53%
See 2 more Smart Citations
“…SLPs even employ many of the same practices as behavior analysts, including the frequent use of single‐subject analysis (Thompson, 2006), antecedent manipulation (i.e., prompting, modeling; Keenan, 1966; Lowell et al., 1995, Thompson et al., 2006), fading (Salvatore, 1976; Melodic Intonation Therapy [MIT]; Sparks & Holland, 1976), shaping (Holland & Harris, 1968; Silkes et al., 2019), and consequence delivery (Goldfarb, 2006; Holland & Harris, 1968; Kushner et al., 1973). This SLP work provides additional empirical support for the efficacy of operant techniques in aphasia treatment that is also demonstrated in purely behavioral work (e.g., chaining, delayed feedback, socially and self‐mediated consequences, and differential reinforcement; Doyle et al., 1989; Goodkin, 1969; Porsteinsson & Sigurðardóttir, 2007; Sigurðardóttir & Sighvatsson, 2006, 2011; Sundberg et al., 1990).…”
Section: A Behavioral Approach To the Treatment Of Aphasiamentioning
confidence: 53%
“…Brain injury subpopulations may also present predictably similar differential training needs. For example, Sigurðardóttir and Sighvatsson (2011) replicated Sigurðardóttir and Sighvatsson's (2006) effective treatment package targeting intraverbals and tacts and was unable to replicate results for all participants, noting differences in initial deficits. Similarly, the extension of the study found backward chaining ineffective for teaching tacts, in contrast to Porsteinsson and Sigurðardóttir (2007), who found improvement from a backward chaining intervention, likely due to participants in the former study lacking an echoic repertoire, while the latter did not.…”
Section: A Behavioral Approach To the Treatment Of Aphasiamentioning
confidence: 99%
See 1 more Smart Citation
“…O uso de procedimentos de ensino com poucos erros para a população afásica também já foi descrito na literatura como benéfico na recuperação de palavras em tarefas de nomeação (Conroy et al, 2009a;2013;Middleton & Scwartz, 2013;Sigurdardottir & Sighvatsson, 2006;Sigurdardottir & Sighvatsson, 2011). O ensino sem erros promove a aprendizagem sem provocar comportamentos emocionais indesejáveis, além dos demais efeitos da ocorrência de erros discutidos anteriormente, como a persistência nos erros e a demora na aprendizagem de discriminações (Melo et al, 2014;Terrace, 1963 Os estudos sobre intervenção com pacientes afásicos descritos em outras seções dessa tese, e que relatam resultados positivos, apresentavam duração semelhante ao do presente estudo, com intervenções de cerca de um ou dois meses, com duas a três sessões por semana (e.g., Conroy et al, 2009a;Conroy et al, 2009b;Conroy et al, 2009c;Leonard, Rochon, & Laird, 2008;Park et al, 2013;Raymer et al, 2007;Wanbaugh et al, 2002).…”
Section: Desempenhos Nas Tarefas De Leitura (Gh) Dos Estímulos Indefiunclassified
“…A maioria dessas pesquisas, porém, relata sessões de duas a três horas, o que se diferencia muito da duração das sessões realizadas neste trabalho, que tinham, em média, duração de 20 minutos. Algumas outras pesquisas apresentadas aqui realizaram intervenções mais longas, com durações que variavam entre seis meses e um ano de sete meses (Kunst et al, 2013;Sigurdardottir & Sighvatsson, 2006;Sigurdardottir & Sighvatsson, 2011). Entretanto, há estudos que descrevem bons resultados com terapias intensivas, realizadas em cerca de 10 sessões, com duração de duas semanas (Bilda, 2011;Bonifazi et al, 2013;Pulvermüller et al, 2013).…”
Section: Desempenhos Nas Tarefas De Leitura (Gh) Dos Estímulos Indefiunclassified